Molecular Analyses of the Platelet Glycoprotein Ib-IX-V Receptor - Ware, Jerry (Thrombosis and Haemostasis, 1998)
Glycoprotein receptors within the platelet membrane are essential for initiating platelet adhesion and aggregation on thrombogenic surfaces. As a response to vascular injury these receptors provide platelets with two essential properties i) the ability to bind adhesive substrates exposed at the site of injury (adhesion) and ii) the ability to recruit additional platelets to form a thrombus (aggregation). It is becoming increasingly evident that defined rheological conditions govern the physiological relevance of specific receptor-ligand interactions along with fundamentally distinct molecular mechanisms for individual receptors and their ligands. Among platelet receptors the glycoprotein (GP) Ib-IX-V complex is important because it initiates thrombus formation over a wide range of flow conditions through an initial interaction with the adhesive ligand, von Willebrand factor. The importance of this receptor-ligand interaction is best exemplified by congenital bleeding disorders resulting from the lack of either the receptor or the ligand, the Bernard-Soulier syndrome and von Willebrand disease, respectively. Additionally, the GP Ib component of the GP Ib-IX-V complex contains a binding site for α-thrombin and recent studies have strengthened the concept that the interaction between α-thrombin and GP Ib is of biological relevance. Unquestionably, studies dissecting the GP Ib-IX-V complex are defining essential aspects of normal hemostasis and thrombosis while providing key information on the molecular mechanisms governing the formation of pathologic platelet thrombi. This review will summarize recent advances in our understanding of the synthesis, structure and function of the platelet GP Ib-IX-V complex. Where possible, directions for future studies will be identified with an overall goal of achieving a more complete understanding on the role of the GP Ib-IX-V complex in platelet biology.